Review: Franz Breuer with Assistance of Barbara Dieris and Antje Lettau (2009). Reflexive Grounded Theory. Eine Einführung für die Forschungspraxis [Reflexive Grounded Theory: An Introduction to Research Praxis] - Da Rin, Sandra (Forum, qualitative social research, 2010)
This textbook by Franz BREUER, produced with the assistance of Barbara DIERIS and Antje LETTAU, is of interest more for the introduction it provides to reflexive research praxis than to grounded theory methodology. This means the subjectivity of the researcher is included in the research process as a decisive source of cognition. Reflexive grounded theory methodology is characterized by three elements that also structure the textbook. In the present review, I focus on two of these in detail: the approach to the research field based on ethnography, particular its epistemological prerequisites, and the inclusion of (self-) reflexivity. The latter points to questions that are addressed at the end of this review. [PUBLICATION ABSTRACT]